Prestigious publications and public relevance: Vietnam war and black protest in the ASR and APSR - Petras, James F. (Crime, law and social change, 1992)
This study examines the manner and the extent to which the social sciences are prepared to address large scale, long term historical change. Particularly, the American Political Science Review and the American Sociological Review are subjected to a content analysis with regards to their analyses of the Vietnamese war and the Black uprisings of the 1960s. The results identify the fact that the most preeminent social science journals failed to analyze the conflicts; either prior to, during or after their emergence. This suggests, at a general level, that critical reflection of the dominant theoretical paradigms of social science did not take place. Moreover, it is suggested, on a more specific level, that the fundamental problem was the bankruptcy of the 1950s paradigm for the 1960s and the incapacity of the more influential journals to identify, address and overcome this intellectual limitation.